Short term interval training improves mitochondrial respiration and exercise capacity - Gant, N.; Vincent, G. E.; Edge, J. A.; Vincent, P. J.; MacDonald, J.; Hickley, A. J. R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Low volume high-intensity interval training (HIT) is a potent exercise strategy that stimulates metabolic adaptation in humans. However, current training protocols consisting of repetitive `all out` maximal sprinting efforts of ~30 s require a high level of participant motivation and specialized laboratory equipment. Recently, a more practical HIT model has been introduced involving tolerable intensity and extended duration bouts, which are interspersed with appropriate recovery periods. The influence of HIT on mitochondrial respiration has yet to be studied. Method: Here we use groups of matched males and females to show the effects of HIT over a short period (2 weeks) on whole body and mitochondrial respirometry, skeletal muscle performance, and cellular adaptation. Eight men and eight women (age 22 ± 2 y, body mass 75 ± 14 kg) performed one-legged VO2 peak tests with bilateral muscle biopsies (vastus lateralis) taken before and after two weeks of HIT. Training involved single-leg cycling using the non-exercising leg as the control. Exercise bouts were performed 4 days/week and comprised 12 x 1 min intervals at 120% of peak power output performed during VO2 peak tests, separated by 90 s of rest. Mitochondrial respiration and the activity of enzymes citrate synthase and lactate dehydrogenase were quantified. Results: Training increased peak power in the trained limbs of both males (22.9%) and females (45.9%) (P < 0.05). Maximal oxidative phosphorylation capacities improved in male participants (20.7%), as did cytochrome c-oxidase respiration (12.9%) and citrate synthase activity (79.6%) (P < 0.05 for all). Apparent enhancements in mitochondrial and enzymatic function failed to reach statistical significance in females. Baseline training status, antioxidant capacities and stress-induced responses may explain the gender differences. Conclusion: HIT is a time-efficient training method that can improve exercise capacity and mitochondrial function over a 2-week period.